A severe microsporidian disease in cultured Atlantic Bluefin Tuna (Thunnus thynnus) - Alejandro López-Verdejo; Francisco E. Montero; Fernando de la Gándara; Miguel A. Gallego; Aurelio Ortega; Juan Antonio Raga; José F. Palacios-Abella (IMA Fungus)
Abstract One of the most promising aquaculture species is the Atlantic bluefin tuna (Thunnus thynnus) with high market value; disease control is crucial to prevent and reduce mortality and monetary losses. Microsporidia (Fungi) are a potential source of damage to bluefin tuna aquaculture. A new microsporidian species is described from farmed bluefin tunas from the Spanish Mediterranean. This new pathogen is described in a juvenile associated with a highly severe pathology of the visceral cavity. Whitish xenomas from this microsporidian species were mostly located at the caecal mass and ranged from 0.2 to 7.5 mm. Light and transmission electron microscopy of the spores revealed mature spores with an average size of 2.2 × 3.9 μm in size and a polar filament with 13–14 coils arranged in one single layer. Phylogenetic analysis clustered this species with the Glugea spp. clade. The morphological characteristics and molecular comparison confirm that this is a novel microsporidian species, Glugea thunni. The direct life-cycle and the severe pathologies observed makes this parasite a hard risk for bluefin tuna cultures.